Are firm innovativeness and firm age relevant for the supply of vocational training? A study based on Swiss micro data - Spyros Arvanitis (The Open Economics Journal, 2010)
In this study we investigated the determinants of the propensity of Swiss firms to train apprentices. Innovation, firm age and competition conditions on the product market are determining factors that were especially emphasized in this investigation. We found that the skill composition of the employment, innovation activities, firm age, labour costs, capital intensity, and competitive pressures all play a discernible role, even if not at the same extent, in determining the propensity of apprentice training. The data used in this study were collected in the course of four surveys among Swiss enterprises in the years 1996, 1999, 2002 and 2005 using a questionnaire which included besides questions on basic firm characteristics also several innovation indicators. New elements of the analysis that distinguish it from already done work on this subject, especially in Switzerland, are: (a) the focus on the role of innovation and firm age for apprentice training; (b) the consideration of effects of competition on the product market; (c) the separate investigation of three sectors of the economy (manufacturing; services; construction); (d) the wide spectrum of determinants of training propensity that are taken into consideration; (e) the use of a panel of firms covering a period of about ten years (1995-2004).
Keywords: 330; apprentice training; innovation; firm age